Ovarian Cancer Screening - Edward J. Pavlik (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Presented here are scientific reports which add considerable information to the area of early stage ovarian cancer detection and the application of this detection to ovarian cancer screening. In this volume, the following presentations are made: 1) The performance of different ultrasound-based International Ovarian Tumor Analysis (IOTA) strategies is analyzed to discriminate between early stage ovarian malignancy and benign abnormalities of the ovary. 2) Since oophorectomy confers protection against ovarian cancer, when adjustment for oophorectomy was made, rates of ovarian cancer were substantially higher. 3) The frequency of symptoms relevant to ovarian cancer was found to be more than two-hundred times higher than the occurrence of ovarian cancer and it was found that 80.1% of women expressed confidence in the symptoms they reported. 4) Complications resulting from surgery performed in the Kentucky Ovarian Cancer Screening Program were infrequent and significantly fewer than reported in the Prostate, Lung, Colorectal and Ovarian Cancer Screening trial. Complications observed were mostly minor (93%) and were more common in cancer versus non-cancer surgery. 5) Arguments in favor of serial ultrasonography as an alternative to immediate surgery are presented and illustrate the benefits of surveillance. 6) Ten critical considerations for ovarian cancer screening are presented in depth, highlighting their important bearing on ovarian screening outcomes and their interpretations. 7) Considerations that have psychological and behavioral impacts on individuals participating in ovarian screening suggest that a "normal" screening test result can have psychological benefits, including an increased positive effect and beliefs in the efficacy of screening. 8) The efficacy of ovarian cancer screening may be higher in Asia than in Europe and the USA. Additionally, the re-analysis of PLCO screening data, when cancers presenting more than one year after screening are excluded, shows a significant survival benefit in the PLCO screening trial. 9) The effect that ovarian cancer has on patients and their families is examined from the perspective of a first-year resident in Obstetrics and Gynecology. 10) The 50-year history of biomarkers and ultrasound in the context of ovarian cancer indicates the importance of serial application of both biomarkers and ultrasound. Taken together, this volume provides both original data and overviews of ovarian cancer screening studies that enhance the present interpretation of this type of screening.